Physical Activity Knowledge, Attitude, and Practice Among Pregnant Women Attending Maternal Health Care Service in Eastern Ethiopia - Reyad Shek Adem; Aboma Motuma; Behailu Hawulte Ayele (SAGE Open Nursing)
Background Physical activity is associated with a reduced risk of several adverse obstetric outcomes, including preterm birth, gestational diabetes, and preeclampsia, anxiety, and depression. However, the majority of women do not achieve recommended levels of physical activity in either time or intensity. It was less known among pregnant women in Ethiopia. This study assesses the knowledge, attitude, and practice of physical activity among pregnant women attending antenatal care in Harari regional state, eastern Ethiopia from December 15, 2023 to January 15, 2024. Methods An institution-based cross-sectional study was conducted among 435 participants. A random sampling method was deployed to select study participants. A pretested and structured questionnaire was used to collect the data through a face-to-face interview. Data were entered into EpiData version 3.1 and analyzed using SPSS 26.0 software. Binary logistic regression was used to identify factors associated with physical activity practice. Adjusted odds ratio (AOR) with a 95% confidence interval was used to report the association, and statistical significance was declared at p-value < 0.05. Results The findings indicate that 50.1% (95% CI: 45.5–54.9%) of pregnant women were practice physical activity. Women attending health centers (AOR = 2.81, 95% CI: 1.85–4.26), aged 25–34 years (AOR = 1.94, 95% CI: 1.25–3.02), urban residence (AOR = 1.85, 95% CI: 1.17–2.91), and women with good perceived benefits (AOR = 4.78, 95% CI: 3.12–7.31) were significantly associated with physical activity. Conclusion The findings reveal that half of the study participants practice physical activity. Attending health centers, the age of women, residence, and positive perception of the benefit of physical activity were significantly associated with physical activity. Nurse practitioners should educate women about the benefits of regular physical activity and help them overcome the barriers to achieving recommended physical activity levels to improve perinatal outcomes.